PENDIDIKAN ISLAM MULTIKULTURAL DI PESANTREN (Studi Kasus pada Pondok Modern Ittihadul Ummah Gontor Poso) - Jihan Jihan (ISTIQRA, 2014)
This study discusses the Multicultural Islamic education applied in Modern Islamic Boarding school Ittihadul Ummah in Poso. The method used in this research is descriptive method. The study design was a descriptive qualitative. The data were analyzed, using data reduction, data presentation, and data verification either inductive, deductive and comparative. The results showed that the Modern Islamic Boarding school Ittihadul Poso has instilled multicultural education to the students. This is illustrated by the religious values are imparted to the students such as brotherhood (fraternity), ta'awun (cooperation), jihad (struggle) that are all taught equality of human rights. The real form of Modern Islamic Boarding school Poso in embed multicultural education can be demonstrated by students- who come from various regions and districts in Central Sulawesi, and some even come from other provinces. These students live in dormitories under the guidance of clerics and preachers who also stayed the same boarding complex environment with the students. This illustrates the unity, brotherhood, and beautifully framed cooperation with mutual respect human regardless of ethnicity, race, and culture of students